Measuring Annual Variation in Reproductive Output Reveals a Key Role of Maternal Body Condition in Determining the Size of Eggs in Snakes - Kun Guo; Xiang-Mo Li; Yan-Qing Wu; Yan-Fu Qu; Xiang Ji (Animals, 2022)
Long-term studies are especially suited for disentangling the effects of extrinsic and intrinsic factors on both total reproductive investment and reproductive allocation in offspring number versus offspring size. Female reproductive traits of the red-banded wolf snake (Lycodon rufozonatus) from Zhejiang, East China were studied in four years between 1999 and 2014. Egg-laying dates overall extended from late June to late July, and varied among years. Postpartum body mass, clutch size, clutch mass, and egg size were positively related to female size (snout vent length, SVL) in each year. Postpartum body mass, clutch mass, and egg size differed among years after accounting for female SVL, whereas clutch size did not. Setting female SVL at the same level, postpartum body mass was greater in 2010 than in 2014, clutch mass was greater in 2010 than in 2011 and 2014, and egg size was greater in 2010 than in the other three years. Females did not trade off egg size against number. Egg size was positively related to postpartum body condition in each year. Females laid larger eggs in 2010 than in other three years after removing the influence of maternal body condition. Our study provides evidence for the traditional view that reproductive output is highly linked to maternal body size in snakes, but not following Smith and Fretwell’s (1974) classic prediction that females with different amounts of resources to invest in reproduction should give priority to adjusting the number rather than size of their offspring. Maternal body size and condition both are important sources of variation in egg size, but factors other than these two variables may also affect the size of eggs produced by female L. rufozonatus.